2014
DOI: 10.4049/jimmunol.1303012
|View full text |Cite
|
Sign up to set email alerts
|

IDO2 Is a Critical Mediator of Autoantibody Production and Inflammatory Pathogenesis in a Mouse Model of Autoimmune Arthritis

Abstract: Rheumatoid arthritis (RA) and other autoimmune disorders are associated with altered activity of the immunomodulatory enzyme indoleamine-2,3-dioxygenase (IDO). However, the precise contributions of IDO function to autoimmunity remain unclear. Here, we examine the effect of two different IDO enzymes, IDO1 and IDO2, on the development of autoimmune arthritis in the KRN preclinical model of RA. We find that IDO2, not IDO1, is critical for arthritis development, providing the first direct evidence of separate in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(156 citation statements)
references
References 61 publications
7
149
0
Order By: Relevance
“…These enzymes are capable of exhibiting similar [23,24,35], opposing [37,38] or co-operative [25] biological actions. Furthermore, although it is clear that targeting IDO1 activity with the D-or L-isomers of 1-MT underlies the ability of the drug to modulate numerous physiological and pathophysiological conditions in experimental animals, questions regarding the specificity of 1-MT (and other IDO1-targeted small-molecule inhibitors) for IDO1 compared with IDO2 both in vitro and in vivo remain to be clarified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes are capable of exhibiting similar [23,24,35], opposing [37,38] or co-operative [25] biological actions. Furthermore, although it is clear that targeting IDO1 activity with the D-or L-isomers of 1-MT underlies the ability of the drug to modulate numerous physiological and pathophysiological conditions in experimental animals, questions regarding the specificity of 1-MT (and other IDO1-targeted small-molecule inhibitors) for IDO1 compared with IDO2 both in vitro and in vivo remain to be clarified.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest differential and non-redundant functions of IDO2 in vivo that are only now beginning to be revealed. For instance, recent data support the suggestion that IDO2, but not IDO1, is linked to the pathogenesis of arthritis in mice by promoting the production of autoantibodies [37], whereas, unlike IDO1, IDO2 is not involved in the progression of inflammatory skin cancer in a mouse model [38]. Despite this discrepancy in the roles of IDO1 and IDO2, IDO2 can act similarly to IDO1 in promoting the generation of immunosuppressive Tregs (regulatory T-cells) and Ido1 and Ido2 gene-deficient mice both exhibit reduced skin-contact hypersensitivity responses [35,38].…”
Section: Ido1 and The Kyn Pathway Of L-trp Metabolismmentioning
confidence: 90%
See 1 more Smart Citation
“…À/À mice show less severe inflammation of joints in a model of rheumatoid arthritis (36). These mice also have less intense hypersensitivity reactions and a reduced capacity to produce inflammatory cytokines and Tregs.…”
Section: Ido2mentioning
confidence: 99%
“…In a rheumatoid arthritis inducible mouse model (KRN g7 B6), our institute has shown that deletion of the IDO2 gene alleviates arthritis [77]. IDO2 knockout (ko) KRN g7 mice were shown to have a significant delay in the onset of arthritis and an overall reduction in the amount of ankle swelling compared with KRN g7 and IDO1 ko KRN g7 mice.…”
Section: The Indoleamine 23-dioxygenase Pathway Mechanism Of Immune mentioning
confidence: 99%